Electromechanical energy devices and power systems - Yamayee, Zia A. (John Wiley and Sons, 1994)
Energy resources and electric energy conversion. Power system components and analysis. Basic AC circuit concepts. Magnetic circuits and transformers. Fundamentals of rotating machines...